2022
DOI: 10.1002/marc.202200424
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Oxyanionic Polymerization of Propylene Oxide: Unlocking the Molecular‐Weight Limitation by a Soft Nucleophilic Catalysis

Abstract: The oxyanionic ring-opening polymerization of propylene oxide (PO) from an exogenous alcohol activated with benign (complexed) metal-alkali carboxylates is described. The equimolar mixture of potassium acetate (KOAc) and 18-crown-6 ether (18C6) is demonstrated to be the complex of choice for preparing poly(propylene oxide) (PPO) in a controlled manner. In the presence of 18C6/KOAc, hydrogen-bonded alcohols act as soft nucleophiles promoting the PO S N 2 process at room temperature and in solvent-free condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Initial studies confirmed the importance of this adduct interaction 26 , since this mechanism occurs entirely through hydrogen bonding between the propagating alcohol end-group and the acetate base. Despite the slow initial 18C6/KOAc/BnOH supramolecular organization by monomer molecules, the intermediate species formed plays a key role in increasing polymerization control and while both homopolymerizations are characterized by a long inhibition period, regardless of the nature of the initiator used, the polymerization kinetics exhibit similar profiles.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Initial studies confirmed the importance of this adduct interaction 26 , since this mechanism occurs entirely through hydrogen bonding between the propagating alcohol end-group and the acetate base. Despite the slow initial 18C6/KOAc/BnOH supramolecular organization by monomer molecules, the intermediate species formed plays a key role in increasing polymerization control and while both homopolymerizations are characterized by a long inhibition period, regardless of the nature of the initiator used, the polymerization kinetics exhibit similar profiles.…”
Section: Resultsmentioning
confidence: 93%
“…Before copolymerizations were undertaken, we first investigated the homopolymerizations of PO and AGE in bulk at room temperature from a benzyl alcohol (BnOH) initiator activated by 18C6/KOAc complex ([BnOH] 0 /[18C6/KOAc] 0 = 2). Our group previously reported that 15 days were required to homopolymerize PO at 21 °C to get a degree of polymerization (DP = [PO] 0 /[OH] 0 ) of 130 26 . Therefore, to reduce the reaction time, low molecular weight PPO and poly(allyl glycidyl ether) (PAGE) were prepared by targeting a degree of polymerization (DP = [M] 0 /[BnOH] 0 , with M, the monomer employed, i.e., PO or AGE) of 25.…”
Section: Resultsmentioning
confidence: 99%
“…Before copolymerizations were undertaken, we first investigated the homopolymerizations of PO and AGE in bulk at room temperature from a benzyl alcohol (BnOH) initiator activated by 18C6/KOAc complex ([BnOH]0/[18C6/KOAc]0 = 2). Our group previously reported that 15 days were required to homopolymerize PO at 21 °C to get a degree of polymerization (DP = [PO]0/[OH]0) of 130 26 .…”
Section: Homopolymerizations Of Propylene Oxide and Allyl Glycidyl Ethermentioning
confidence: 99%
“…To determine whether the nature of the initiator molecule impacts the initiation step, we examined the homopolymerizations using isopropyl alcohol (iPrOH Initial studies confirmed the importance of this adduct interaction 26 , since this mechanism occurs entirely through hydrogen bonding between the propagating alcohol end-group and the acetate base. Despite the slow initial 18C6/KOAc/BnOH supramolecular organization by monomer molecules, the intermediate species formed plays a key role in increasing polymerization control and while both homopolymerizations are characterized by a long inhibition period, regardless of the nature of the initiator used, the polymerization kinetics exhibit similar profiles.…”
Section: Homopolymerizations Of Propylene Oxide and Allyl Glycidyl Ethermentioning
confidence: 99%
See 1 more Smart Citation